EFFECT OF RATIONS ON THE DEVELOPMENT OF EXCESSIVE BODY WEIGHT OF MEDIUM-BREED DOGS - Lokes-Krupka, T. P.; Burda, T. L.; Tsvilikhovsky, M.I. (Scientific Progress & Innovations, 2019)
According to current research of medical and veterinary scientists and practitioners, primary obesity (nutritional) is usually the result of excessive consumption of easily digestible products (feeds) against the background of malaise. That is why we have studied the influence of different quality rations on the devel-opment of excessive body weight. The influence of excessive and unnormal feeding of domestic dogs of medi-um breed (pug) on rations of various classes on the metabolism of lipids and proteins, as well as morpho-metric characteristics, was investigated. The experiment was conducted for four months as to the influence of dosage of various classes’ rations (natural, industrial rations of super-premium and economy classes) on changes in the animals’ appearance (deposition of abdominal fat) and the state of protein and fat metabo-lism of domestic dog pug breeds. At the beginning of the study, two months and four months later, clinical studies, morphometric calculations, biochemical studies of serum (serum definitions of total protein and fractions, triglycerols, total cholesterol, high, low and very low density lipoprotein) were obtained. During the study we have established deterioration of blood serum values in animals at feeding with fodder of econ-omy class, even normalized. After the second stage of the experiment against the background of hyperproteinemia and increase in dogs body weight by 1.22 times was observed, the state of lipid metabolism deteriorated to a greater extent, compared with the indices after the Ist stage. In the blood serum of dogs, the concentration of triglycerols and LVLD has increased by 1.31 times, total cholesterol and LLD by 1.2 and 1.57 times, respectively. At the end of the second stage of the experiment, as morphometric (body mass increase by1.14 times), the biochemical parameters of the dogs have also undergone certain changes: the protein content of the blood serum has increased; the level of triglycerides, total cholesterol and LHD has increased by 1.31, 1.23 and 1.23 times, respectively. The possibility of developing alimentary obesity in dogs of the average size breeds, namely the pug was experimentally proved. Dogs have constant access to the feed, regardless of the class and type of rations. The morphometric indices and biochemical characteris-tics of blood serum of pug breed domestic dogs for excessive fatness are offered. The obtained research re-sults can be used for practicing doctors of veterinary medicine, as well as in educational activities – to pro-mote rational and dosed feeding of animals.